Pertanggungjawaban Hukum Peminjaman Nama Perusahaan Untuk Mengikuti Pengadaan Barang Dan Jasa Pemerintah - Sunoto, Sunoto; Tjoanda, Mery; Berlianty, Teng (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: The practice of using another company's name to participate in government procurement contracts is a common occurrence today. Although there are no explicit regulations prohibiting this practice, borrowing another company's name can be done due to affiliations between related companies or as an attempt to deceive the bidding organizers.Purposes of the Research: This research aims to examine and analyze the legitimacy of the practice of borrowing a company's name to participate in government procurement of goods and services, as well as the forms of accountability for breaches of contract in the implementation of such name borrowing in procurement processes.Methods of the Research: This research is a normative juridical research, using a descriptive analytical research type using primary, secondary and tertiary legal sources. The approach used is a statutory approach (Statute Approach), a conceptual approach (conceptual approach) and a case approach (Case Approach). The technique of collecting legal materials uses a literature study which is then analyzed qualitatively in order to answer the problems studied.Results of the Research: The research findings indicate that the practice of using another company's name in government procurement of goods and services violates various legal provisions, including Presidential Regulation No. 16 of 2018, Regulation of the Procurement Policy Agency (LKPP) No. 9 of 2019, as well as the Law on the Prohibition of Monopoly Practices and Unfair Business Competition. This practice also fails to meet the requirements of a valid agreement as it contradicts the law. The winning company of the tender is fully responsible for the contract's implementation, including if it utilizes another company's name, and can be sued by the aggrieved party in case of breach of contract, with legal consequences including compensation, contract termination, administrative sanctions, blacklisting, and criminal penalties.